ANALYSIS OF CRITERIA FOR ENSURINGINFORMATION SECURITY OF SCIENTIFIC AND EDUCATIONAL RESOURCES - Rakhmatullaev, Marat; Normatov, Sherbek (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
At present, information and knowledge in the field of science and education are strategic resources. From their formation, renewal, distribution depends not only the scientific and educational spheres, but also the socio-economic development of the country. Therefore, the confidentiality, integrity and accessibility of databases of a scientific and educational nature are an important subject of research. The purpose of this article is to conduct an analysis of methods, criteria for assessing units of scientific information in terms of ensuring information security. Classification of criteria for the evaluation of scientific and educational information (SEI), their systematization, analysis of problem of ensuring the security of information resources are given. Also, the information infrastructure development indicators and projects implemented in the field of information security are outlined. Evaluation of SEI units is carried out by experts who themselves have a weighting factor and are dependent on their qualifications. The results of the research are the basis for the creation of an automated system for ensuring information security in the corporate library system of academic libraries. The corporate network forms an electronic public library, distributes the SEI between resource users. The information security system will ensure the regulation of access to resources.